(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
The process of compaction is not enough to improve the properties of soil particularly in arid and semi arid regions. To enhance the strength and reduce the sensitivity to water change of weak clay deposits, lime and sodium silicate stabilization can be used. The soil stabilization process first involves adding suitable additive to the soil which first changes its properties and then compacting soil admixture suitably. The soil stabilization method is used only for the soils in shallow foundations or the base course of roads, airfield pavements etc. The properties of a soil changes with the usage of lime to give long term permanent strength and stability especially when exposed with water and frost. The degree of reactivity with lime and the ultimate strength that the stabilized layers will develop can be determined by the mineralogical properties of the soils. Recommended percentage of lime for Soil stabilization varies from 2% to 10%. For coarse soils such as clay gravels, sandy soils with less than 50% silt- clay fraction, the recommended percentage of lime varies from 2% to 5%, whereas for soils with more than 50% silt clay fraction, the recommend